ANÁLISE DAS CÉLULAS HEMATOLÓGICAS E DO METABOLISMO DO FERRO NA ASPERGILOSE PULMONAR CRÔNICA - NATHÁLIA ANTUNES MACIEL (2025)
Chronic pulmonary aspergillosis (CPA) is a fungal infection caused by Aspergillus spp., often observed in patients with preexisting lung lesions, such as those resulting from pulmonary tuberculosis (TB) and other pulmonary infections. Typical symptoms include chronic cough, weight loss, dyspnea, hemoptysis, and hemoptoic sputum. This study aims to understand the impact of CPA on hematological cells and iron metabolism in affected patients. Data from a cohort of 14 CPA patients treated between January 2016 and July 2024 at the Maria Aparecida Pedrossian University Hospital in Campo Grande-MS were analyzed. The inclusion criteria involved patients aged 18 or older, diagnosed with CPA, whose laboratory tests were analyzed at two time points: at the beginning of treatment and after six months of itraconazole use. Clinical variables and laboratory tests were assessed, including hemogram, C-reactive protein (CRP), serum iron, total iron-binding capacity (TIBC), transferrin saturation index (TSI), ferritin, hepcidin, and interleukin-6 (IL-6). Statistical tests used for analysis were the Shapiro-Wilk normality test, chi-square, Student's t-test, Mann-Whitney test, Pearson or Spearman correlation coefficient, with a significance level set at p < 0.05. At the start of treatment, 57.1% of patients had anemia, with leukocytosis observed in 35.7% of cases. Relative lymphopenia was found in 64.3% of patients and relative monocytosis in 42.9%. CRP was elevated in 66.7% of patients, indicating an active inflammatory process. Additionally, 61.5% of patients had iron deficiency, reflecting a disruption in iron metabolism. The main comorbidities associated with patients were pulmonary tuberculosis (TB), which was the most prevalent, followed by chronic obstructive pulmonary disease (COPD), asthma, and pneumonia, which may have contributed to vulnerability to Aspergillus spp. fungal infection. After six months of antifungal treatment, anemia persisted in 54.5% of patients, and CRP remained elevated in more than half of the patients, indicating that the therapeutic response in CPA is slow and does not always lead to the complete resolution of inflammatory markers, along with persistent leukocytosis. The persistence of inflammation is consistent with the literature, which suggests that the treatment of CPA may not fully suppress the inflammatory activity in the first few months, depending on the severity of the pulmonary involvement. Correlations between IL-6 and serum iron and erythrocytes were observed, showing that both are reduced in the inflammatory process. Continuous monitoring of the hematological profile and iron metabolism is crucial for evaluating the response to treatment and the clinical progression of CPA patients. Analysis of inflammatory and hematological parameters can provide important insights into disease progression and the impact of antifungal treatment, which has shown to promote modulation of the inflammatory response, although gradually.